Beta-thalassemia in the paediatric cardiac surgery setting - a case report and literature review. (April 2018) - Richardson, Rebecca; Issitt, Richard; Crook, Richard
Beta (β)-thalassemia is a blood disorder with an incidence of 1 in 100, 000. 1 This case report outlines a patient with β-thalassemia requiring cardiopulmonary bypass (CPB) and the measures taken to ensure an uneventful procedure.